2017
DOI: 10.1177/0363546517741497
|View full text |Cite
|
Sign up to set email alerts
|

20-Year Outcomes of Anterior Cruciate Ligament Reconstruction With Hamstring Tendon Autograft: The Catastrophic Effect of Age and Posterior Tibial Slope

Abstract: Repeat ACL injury after isolated ACL reconstruction is common, occurring in 1 in 3 over 20 years. In the absence of further injury, isolated ACL reconstruction using this technique was associated with good long-term outcomes with respect to patient-reported outcomes and return to sports, regardless of age. However, mild ligament laxity and ACL graft rupture after ACL reconstruction are significantly more common in adolescents, especially adolescent males, compared with adults. PTS of 12° or more is the stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
321
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(332 citation statements)
references
References 53 publications
6
321
2
3
Order By: Relevance
“… 4 , 5 Although considered an invasive surgery, it has been suggested that a slope-decreasing osteotomy is necessary for patients wishing to return to sports or for those who need to restore necessary stability for demanding day-to-day activities after a failed ACLR and who have a tibial slope ≥12°. 4 , 5 , 8 This is because it has been reported that increased tibial slope is directly correlated to increased anterior tibial translation, and has been shown to increase the forces experienced by the native ACL. 1 , 3 , 9 , 10 Clinical studies have supported these biomechanical findings, because an increased tibial slope has been reported to increase the risk of ACL graft failure, namely those ≥12°.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Although considered an invasive surgery, it has been suggested that a slope-decreasing osteotomy is necessary for patients wishing to return to sports or for those who need to restore necessary stability for demanding day-to-day activities after a failed ACLR and who have a tibial slope ≥12°. 4 , 5 , 8 This is because it has been reported that increased tibial slope is directly correlated to increased anterior tibial translation, and has been shown to increase the forces experienced by the native ACL. 1 , 3 , 9 , 10 Clinical studies have supported these biomechanical findings, because an increased tibial slope has been reported to increase the risk of ACL graft failure, namely those ≥12°.…”
Section: Discussionmentioning
confidence: 99%
“…PTS is correlated by an ensuing increased occurrence of non-contact ACL injuries in patients with a greater PTS( 9.39° ± 2.58°) relative to control subjects, (8.50° ± 2.67° (p =0.003)). 144 And in activities involving large compression forces, newer studies are showing a significant correlation between ACL re-injury and increased PTS. 19 Salmon et al found adolescent patients (< 18 years) with a PTS of >12° to be a significant predictor of secondary ACL injury.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…19 Salmon et al found adolescent patients (< 18 years) with a PTS of >12° to be a significant predictor of secondary ACL injury. 144 Structural differences of the ligament have also been discussed as a risk factor. The female ligament has less stiffness and less elongation at failure compared to the male ligament.…”
Section: Intrinsic Factorsmentioning
confidence: 99%
“…The same group of Sydneysiders more recently reported a multivariate analysis of factors associated with ACL graft failure in a cohort of 100 males and 100 females followed for 20 years. 27 The principal conclusions of that study are starkly summarized in the article's subtitle, ''The Catastrophic Effect of Age and Posterior Tibial Slope.'' The most remarkable finding: Graft survival in adolescents with a medial tibial slope 12°was a mere 22%.…”
mentioning
confidence: 99%